Effect of spatial variability of engineering properties on stability of a CSMC embankment. Issue 1 (2nd January 2018) - Zhang, Rong-Jun; Hasan, Mohammed Shareef M. S.; Zheng, Jun-Jie; Cheng, Yu-Shi
ABSTRACT: Cement-stabilized marine clay (CSMC), usually used as filling material of coastal facilities such as land reclamation embankments, shows very high spatial variability in engineering properties. This high spatial variability produces substantial influence on the stability of CSMC embankments. In this study, the experimental data collected from an actual project were first analyzed to identify the statistical characteristics of the engineering properties of in situ CSMC. It is shown that the strength of the in situ CSMC follows a lognormal distribution, and the coefficient of variation (COV) is higher than the value (0.35) assumed in the conventional deterministic design method (CDDM). Both deterministic and random numerical analyses were then performed for a typical CSMC embankment. Special attention was paid to evaluate the effects of COV and the mean value of strength on the embankment stability. Results show that the effect of spatial variability is significant but not reasonably accounted for in situ CDDM. This leads to unsafe design when COV >0.35. It is recommended that a larger global safety factor should be chosen for a higher COV to guarantee a target failure probability in future design.